MAPPING THE EVOLUTION AND CURRENT TRENDS HUMANISTIC PEDAGOGIC: BIBLIOMETRIC ANALYSIS - Huda, Miftakul Huda; Siswanto, Budi Nur Siswanto; Utama, RD Dian; Christianingrum, Christianingrum; Komara, Esi Fitriani (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2023)
This bibliometric analysis is aimed at research on pedagogic humanism. Data sources were taken from the Scopus database, with the topic of discussion on Education and training, from searches for the words "Pedagogic" and "Humanist" and "Management", which were in English, looking for articles that were finally published. From the results of data analysis, 1,548 articles were obtained, and were analyzed. The results reveal a significant increase in the number of research publications starting from 1974 to 2023, and the United States is the country that has published the most articles on Pedagogic Humanism. The most dominant keywords used are presented by VOSViewer, there are 6 clusters consisting of: Keywords from the authors "Curriculum," "Student," "educations," "simulations," "pedagogy," and "learning,".